2023
DOI: 10.1177/20552173221150370
|View full text |Cite
|
Sign up to set email alerts
|

Treatment preferences in relation to fatigue of patients with relapsing multiple sclerosis: A discrete choice experiment

Abstract: Background Treatment decisions for multiple sclerosis (MS) are influenced by many factors such as disease symptoms, comorbidities, and tolerability. Objective To determine how much relapsing MS patients were willing to accept the worsening of certain aspects of their MS in return for improvements in symptoms or treatment convenience. Methods A web-based discrete choice experiment (DCE) was conducted in patients with relapsing MS. Multinomial logit models were used to estimate relative attribute importance (RAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This analysis used data from a web-based DCE that assessed treatment preferences of adults with active RMS, including clinically isolated syndrome (CIS), RRMS, or active SPMS (currently under review at Multiple Sclerosis Journal—Experimental, Translational and Clinical ). 12 The DCE was conducted in the United States, United Kingdom, Poland, and Russia. Here, we describe additional analyses based on that DCE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis used data from a web-based DCE that assessed treatment preferences of adults with active RMS, including clinically isolated syndrome (CIS), RRMS, or active SPMS (currently under review at Multiple Sclerosis Journal—Experimental, Translational and Clinical ). 12 The DCE was conducted in the United States, United Kingdom, Poland, and Russia. Here, we describe additional analyses based on that DCE.…”
Section: Methodsmentioning
confidence: 99%
“…The current study aimed to understand the clinical relevance of the difference in fatigue scores between ponesimod and teriflunomide in the OPTIMUM trial. This was achieved by combining data from OPTIMUM and from a recent DCE 12 to determine the number of relapses per year and the change in time to MS progression that patients regarded as equal in importance as the treatment difference in fatigue observed in OPTIMUM. This equivalent relapse rate was contextualized by comparing it to the treatment difference in OPTIMUM.…”
Section: Introductionmentioning
confidence: 99%
“…Tervonen et al observed how they are more willing to endure an increased rate of relapses and accelerated progression in exchange for alleviating cognitive and physical fatigue. This was especially true when considering the ones who had received their diagnosis more than a decade before (Tervonen et al, 2023).…”
Section: Impact Of Fatigue On Quality Of Lifementioning
confidence: 99%
“…Tervonen et al observed how they are more willing to endure an increased rate of relapses and accelerated progression in exchange for alleviating cognitive and physical fatigue. This was especially true when considering the ones who had received their diagnosis more than a decade before (Tervonen et al, 2023 ).…”
Section: Current State-of-the-art In Fatigue In Msmentioning
confidence: 99%